Effect of thermal annealing on electrical and photoelectrical properties of n-InSb - Stariy, S.V.; Sukach, A.V.; Tetyorkin, V.V.; Yukhymchuk, V.O.; Stara, T.R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
InSb wafers of n-type conductivity were annealed at 300, 370, and 400 °C for 30 min in an open tube system under a flowing argon ambient. The conductivity type conversion is revealed for the first time in samples with the electron concentration ~1.0•10¹⁴ cm⁻³ for all annealing temperatures. Experimental evidences have been obtained that this phenomenon has a bulk character. In annealed samples, the spectral response exhibits a pronounced increase in the short-wave region. The effect of annealing on the electrical and photoelectrical properties of n-InSb has been explained by the formation of InSb antisites.